Creative Problem Solving in Intelligent Agents: Domain-Agnostic Methods for Novelty Resolution - Gizzi, Evana. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Computer Science.; Advisor: Jivko Sinapov.; Committee: Daniel Dennett, Conrad Schiff, Elaine Short, and Bert Huang.; Keyword: Artificial intelligence.